2010
DOI: 10.1007/s12094-010-0469-9
|View full text |Cite
|
Sign up to set email alerts
|

Radio-induced bullous pemphigoid

Abstract: We report on the appearance of two new cases of radio-induced bullous pemphigoid (BP), a rare complication of radiotherapy. Both were elderly women, were treated for breast cancer and suffered (BP) during the irradiation, the evolution was favorable with steroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Table 1 provides a summary of patients' profiles, cancer types, lesion characteristics, histology and immunopathology [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. …”
Section: Resultsmentioning
confidence: 99%
“…Table 1 provides a summary of patients' profiles, cancer types, lesion characteristics, histology and immunopathology [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. …”
Section: Resultsmentioning
confidence: 99%
“…4 RT is one of several physical agents including ultraviolet light, thermal burns and skin grafts that have been reported to induce BP in normal skin. 5 Radiation-induced bullous pemphigoid (RIBP) affects mainly women with breast carcinomas, [6][7][8] but it has been reported also with other cancers (vulva, cervix, lung and esophagus). 9 Mul et al, reported a large series of BP associated with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous case reports on ABD and breast cancer including predominantly BP [20,[81][82][83][84][85] and PV [86,87] with well-documented BP-lesion induction with radiotherapy.…”
Section: Malignancies Associated With Abdmentioning
confidence: 99%